The influence of social media marketing towards the repurchase intention with brand image as mediating variable - Fajar; Yunia Wardi (Marketing Management Studies, 2022)
This study aims to analyze (1) the effect of social media marketing on intention to use on MSGlow Redjelly consumers and TiK-ToK users mediated by brand image . (2) the effect of social media marketing on repurchase intention towards MSGlow Redjelly and TiK-Tok user (3) the effect social media marketing on brand image towards MSGlow consumers and TiK-ToK user. (4) the effect of brand image on repurchase intention toward MSGlow consumers and TiK-ToK user. The population used in the study were MSGlow Redjelly consumers and TiK-ToK user that already use the product and using TiK-ToK for some quite time. The number of samples in this study was 251 total respondents. Data was collected through online questionnaires and data processing using PLS (Partial Least Square) software. The results of this study indicate that. (1) Social media marketing has positive but not significantly affecting repurchase intention. (2) Social media marketing has positive and significant effect towards brand image. (3) Brand image has positive and significant effect toward repurchase intention. (4) Social media marketing has positive and significant effect toward repurchase intention mediated by brand image.